Growth rate, feed intake, physiological responses and hormonal profile of Murrah buffaloes implanted melatonin during summer season - KUMAR, PRAMOD; SINGH, S V (The Indian Journal of Animal Sciences, 2021)
In order to find out the effect of melatonin implantation on physiological responses, hormonal profile, feed intake and growth performance, 12 growing Murrah buffaloes were selected. These animals were further divided equally in two groups i.e. control and treatment (melatonin implantation @ 18 mg/50 kg body wt.). Melatonin was implanted subcutaneously in the thoracic region after every 45 days’ interval in treatment group. Body weight and physiological parameters, viz. respiration rate (RR), rectal temperature (RT), pulse rate (PR) were recorded at fortnightly interval. Blood samples were also collected aseptically from both the group of animals at fortnightly intervals and plasma was separated for quantitation of hormones. The physiological responses were found to be significantly lower in treatment group than control group of growing buffaloes. The levels of growth and cortisol hormones were higher in treatment than control group. No significant variation was observed in the IGF-I levels. The melatonin implantation improved the growth rate, ADG and feed intake of growing buffaloes than control group. Based on the results of the present study, it is evident that melatonin implantation to growing buffaloes worked as an antioxidant and lowered the stress levels and enhanced growth rate during heat stress. Higher growth rate in treatment group of growing buffaloes will help in reducing the age of puberty and ultimately increase the total productive life.